Making the Case for Cosmopolitan Pathways for Canada’s Diversity - Sfeir, Ghada (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
This article seeks to develop the argument that it is time for a national roundtable negotiation among Indigenous peoples, the two English and French settler nations, the BIPOC communities and the various immigrant groups to consider the merits of cosmopolitanism as a moral and cultural framework of our interrelated relationships and intercultural encounters in Canada. In an interdependent globalized world that is becoming “superdiverse,” I argue that it is time to shift from the language of “tolerance” of the “Other” to the language of “engagement” with “fellow human beings” guided by the moral and cultural cosmopolitanism for social and global justice, equality and equity, and inclusion through the fulfillment of human rights. The purpose of this public discussion is to urge the Canadian Council of Ministers of Education as well as the federal government to put this question on their agenda for consideration as a new framework for Canada’s educational, social, economic and political policies. This argumentative paper has the potential to benefit policymakers, curriculum designers, educators, and ministries of education across Canada and beyond to consolidate moral and cultural cosmopolitanism as a national and international approach to harmonious human coexistence.